ANTISYNTHETASE SYNDROME: COURSE OF A RARE DISEASE ON EXAMPLE OF CLINICAL CASE - Boateng, H. K.; Babiy, O. G.; Shalkova, R. S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
Systemic disorders of connective tissue refer to rare and poorly studied diseases. This group of diseases associated with the variable course and makes it interesting for either medical scientists and researchers or practitioner. Herein we report a case of antisynthetase syndrome with interstitial lung disease complicated by pulmonary thromboembolism. The patient is 71 year old female, who suffered from severe dyspnea, dry cough, intermittent wheezing. Also she had dry eyes, dry mouth, muscle weakness and intermittent pain in large joints, and low grade fever. Physical examination revealed a characteristic heliotrope eye rash, V sign, «mechanic’s hand», peripheral muscles atrophy, dry eyes and mouth, fine crackles to auscultation in basal parts of lungs, soft S1 and S2 heart sounds. Her biochemical profile showed increased creatinekinase, LDH, AsAT, and AlAT Her immunology results were positive to ANA, anti-ds-DNA, anti-ss-A, anti-ss-B and anti-Jo-1 autoantibodies. Based on the obtained data, antisynthetase syndrome was established. It was detected, that progressive dyspnea had been caused by interstitial lung disease and pulmonary thromboembolism. It was confirmed by chest CT-scan and pulmonary angiography. Treatment in this case is mainly symptomatic. It was prescribed glucocorticoids, immunosuppressant, and anticoagulants. This case illustrates the course of the antisynthetase overlap syndrome and difficulties of it management due to the lack of treatment standards and reliable data of the medicine effectiveness.